Predicting VOC emissions from materials in vehicle cabins: Determination of the key parameters and the influence of environmental factors - Yang, Tao; Zhang, Pianpian; Xu, Baoping; Xiong, Jianyin (International journal of heat and mass transfer, 2017)
•A model is developed to predict VOC emissions under different initial conditions.•A method is proposed to determine the key parameters C0 and Dm of in-cabin material.•C0 and Dm for five VOCs emitted from a common in-cabin material are measured.•Influence of temperature on C0 is firstly investigated for VOCs.•C0 of studied VOCs increases with an increase in temperature and relative humidity. Emission of volatile organic compounds (VOCs) from materials in vehicle cabins is one of the main reasons for poor in-cabin air quality. The emission behaviors can be characterized by key parameters including the initial emittable concentration (C0) and the diffusion coefficient (Dm). Determination of these parameters provides a foundation for predicting emissions and evaluating driver and passenger exposures. By analyzing VOC emissions from in-cabin materials under ventilated conditions, we propose a novel method to simultaneously determine C0 and Dm. This method initially establishes a linear correlation between the logarithm of excess VOC concentration and emission time, then the key parameters C0 and Dm are obtained by linear curve fitting and solving two equations. Using this method we determined the C0 and Dm for five VOCs (benzene, toluene, p-xylene, ethylbenzene and styrene) emitted from a common in-cabin material under different environmental conditions. Good agreement between the predicted VOC concentrations based on the measured key parameters and experimental data demonstrates the effectiveness of this method. Moreover, the impact of temperature on C0 was investigated for the five VOCs. Results indicated that C0 of all the studied VOCs increased with an increase in temperature, and toluene showed the greatest increase. When the temperature increased from 25°C to 50°C at the relative humidity of 50%, the C0 of toluene increased by 1.07 fold.